Recent advances in enhancing the sensitivity of electrophoresis and electrochromatography in capillaries and microchips (2012–2014). Issue 1 (January 2015) - Breadmore, Michael C.; Tubaon, Ria Marni; Shallan, Aliaa I.; Phung, Sui Ching; Abdul Keyon, Aemi S.; Gstoettenmayr, Daniel; Prapatpong, Pornpan; Alhusban, Ala A.; Ranjbar, Leila; See, Hong Heng; Dawod, Mohamed; Quirino, Joselito P.; et al.
<x xml:space="preserve">Abstract</x> One of the most cited limitations of capillary (and microchip) electrophoresis is the poor sensitivity. This review continues to update this series of biannual reviews, first published in Electrophoresis in 2007, on developments in the field of on‐line/in‐line concentration methods, covering the period July 2012–July 2014. It includes developments in the field of stacking, covering all methods from field‐amplified sample stacking and large‐volume sample stacking, through to ITP, dynamic pH junction, and sweeping. Attention is also given to on‐line or in‐line extraction methods that have been used for electrophoresis.